Digestion of Sago Based Diets in Sheep - Muhamad, Yahya (2000)
Sago (Metroxylon sagu, Rott.) pith meal (SPM) can be used as an excellent energy feed for ruminant livestock because the pith contains high amount of starch and some indigenous fibre. However, there is a lack of information on the nutritive properties of SPM and effects of feeding SPM on the digestion parameters of ruminant animal. Therefore, the objectives of the present studies were: to determine the physical and chemical caharacteristics of SPM; and to study the effects of feeding SPM based diets on the growth performance of lambs and on digestibility of the diets , especially in relation to nutrient flows and microbial protein synthesis, in sheep. The experimental diets used were SPM plus soya bean meal (Diet A), SPM plus soya bean meal and urea (Diet B) and SPM plus fish meal and urea (Diet C). The crude protein content of SPM was less than 2% while the neutral detergent fibre (NDF), starch and gross energy (GE) contents on dry weight basis were 12.8%, 72.2% and 1 7.5 MJ/kg, respectively. Scanning electron microscopy revealed that SPM consisted mainly of starch granules, parenchyma cell walls and vascular bundle fibres which were degraded in situ at different rates by the rumen microbes. The digestibility of organic matter in dry matter (DOMD) was similar for all the diets which averaged 77-78%, but the metabolisable (ME) and net energy for fattening (NEJ values were: 10.4, 10.4, 11.0 MJ ME and 7.7, 7.7, 8.0 MJ NEr (P<0.05) per kg of feed dry weight for the three diets, respectively. The performance responses of 21 lambs fed with the three diets showed that their final weights and average daily gains (ADG) were: Diet A, 28.9 kg and 122 g; Diet B, 21.9 kg and 50 g: Diet C, 24.6 kg and 76 g (P<0.05). The efficiencies of microbial protein synthesis measured in terms of g Nlkg starch digested in the rumen for these respective diets were 81.3, 21.9 and 32.3 g (P<0.10). In conclusion, sago-pith meal contains an energy value equivalent to maize grains but having additional benefits from the indigenous fibres which are necessary for cellulolysis and the roughage effect. To improve the efficiency of energy utilization from sago diets, ruminal pH depression due to rapid breakdown of starch need to be sufficiently controlled such as through proper feed processing, ration formulation and feeding regimen.